Manufacturers' implementation of circular economy practices and renewable energy sources in Saudi Arabia's industrial plants - Alqahtani, Mohammed Farhan; Afy-Shararah, Mohamed; Salonitis, Konstantinos (Taylor & Francis, 2026)
A dearth of research has addressed the growing integration of circular economy (CE) practices and renewable energy (RE) sources in industrial settings, motivating the commencement of the present study. The primary objective of this research is to document manufacturers' integration patterns of CE practices and RE sources in industrial plants. To fulfil this goal, the researcher convened two focus groups in Saudi Arabia. Each focus group featured five participants who owned, operated or researched facilities that implemented CE and RE. The findings suggest that four distinct integration patterns define how CE and RE are integrated in industrial settings: (a) biogas with remanufacturing, (b) solar power with recycling, (c) wind power and reducing and (d) the combined use of solar and wind power with more than a single CE practice. Further, results indicate a growing trend of using green practices such as green chemistry with CE practices in manufacturing. The study also reported the presence of numerous facilitators and barriers facing the integration of CE and RE. The current analysis contributes to the growing research on CE and RE aiming to improve sustainability.
Keywords: Circular economy; renewable energy; manufacturing; integration; sustainability; 33 Built Environment and Design; 40 Engineering; 3301 Architecture; 12 Responsible Consumption and Production; 7 Affordable and Clean Energy; 13 Climate Action